MENINGKATKAN MOTORIK KASAR USIA PRASEKOLAH MELALUI GERAKAN TARI PADA KELOMPOK B TK NURANI - Endang Tri Sudaryanti; Kusniati Nursika Sahara; Rohmalina Rohmalina (IKIP Siliwangi, 2018)
This research is aimed at increasing rough motor on early childhood. At early childhood, There are a lot of developmental aspects that must be stimulated and one of this is the rough motor movement. Children’s rough motor movement is the ability of children in moving using big muscles. Nowadays there are schools that focused more on the smooth motor movement such as writing, cutting and others that is due to factors of parents and demands of calistung (reading, writing, and counting) to enter the basic education unit. Rough motor movements become abandoned, but researcher intended to increase children’s motor movement, not only in smooth motor movement but also rough motor movement. One of the activity to increase children’s rough motor movement is through dance activities for childrens. Through this dance movement, children’s rough motor movement can be stimulated and children is given varied instruction, not only doing basic movements such as jumping, running and others but the childrens are also able to perform other dance movements accompanied with music. Therefore children is not only learning but also able to recognize fun dance movements.